Analisis Deteksi Tumbuh Kembang Balita Di Posyandu Lavenda - Susilawati, Susilawati; Junita, Dewi (JURNAL KESEHATAN TERAPAN, 2025)
G Growth is an increase in the size and number of cells and intercellular tissue, meaning an increase in the physical size and structure of the body in part or in whole, so that it can be measured in units of length and weight. Development is an increase in the structure and function of the body that is more complex in gross motor skills, fine motor skills, speech and language, and socialization and independence. The purpose of the study was to analyze deviations in the growth and development of toddlers at the Lavenda Posyandu in Jambi City. This research method uses a descriptive approach with direct observation and data collection through interviews with parents conducted in January 2025. The population in this study were all toddlers aged 1 to 5 years at the Lavenda Posyandu in Jambi City. The sample in this study was 48 toddlers aged 1 to 5 years. Data collection was carried out through the Pre-Screening Development Questionnaire (KPSP). The results of the toddler growth detection study showed normal nutritional status for 43 children (93.75%), thin for 4 children (8.33%) and obese for 1 person (2.08%). Meanwhile, the results of the toddler development detection showed that the results of the child's development were in accordance with their development. Growth and development detection analysis is very important to maximize the optimization of children's growth and development from an early age. Early detection as a form of early intervention in children provides a beneficial effect to prevent deviations in growth and development as early as possible.